Gambaran jenis-jenis penyakit penglihatan mata pada lansia di dusun kembang - Sulistyo, Joko; Kumalasari, Sekar (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Vision disorders in the elderly generally include myopia, presbyopia, glaucoma, and cataracts, Advanced age causes decreased vision. Decreased vision and visual function that are considered normal with the aging process include reduced vision physiology, decreased eye ability to read and color vision. Purpose: To determine the types of eye diseases experienced by the elderly. Method: This research uses a descriptive quantitative method using a cross-sectional design, involving 93 respondents.. Results: Frequency distribution data shows that the gender of respondents is dominated by women with 63 (67.7%) respondents. Based on the age of respondents, the most age range is 51-60 years with 36 (38.71%) respondents. Eye diseases in the elderly are the highest experiencing myopia with 40 (43.3%) respondents, presbyopia with 28 (30.1%) respondents, glaucoma with 14 (15.1%) respondents and those experiencing cataracts with 11 (11.8%) respondents. However, of the elderly experiencing these diseases who use glasses, only 24 (25.8%) respondents. Conclusion: The study concluded that the elderly in Kembang Hamlet experienced various eye diseases such as presbyopia, myopia, cataracts and glaucoma, but only 25.8% used eyeglasses as visual aids.   Keywords: Cataract; Glaucoma; Myopia; Presbyopia.   Pendahuluan: Penyakit penglihatan pada lansia pada umumnya meliputi myopia, presbiopia, glaukoma, dan katarak. Usia lanjut menyebabkan penurunan penglihatan. Penurunan penglihatan dan fungsi penglihatan yang dianggap normal seiring proses penuaan termasuk fisiologi penglihatan yang berkurang, penurunan kemampuan mata untuk membaca dan penglihatan warna. Tujuan: Untuk mengetahui gambaran jenis-jenis penyakit mata yang dialami lansia. Metode: penelitian ini menggunakan metode kuantitatif deskriptif dengan menggunakan desain cross sectional yang melibatkan 93 responden. Hasil: Data distribusi frekuensi menunjukkan jenis kelamin responden di dominasi perempuan sebanyak 63 (67.7%) responden. Berdasarkan usia responden, rentang usia terbanyak yaitu 51-60 tahun sebanyak 36 (38.71%) responden. Penyakit mata pada lansia yaitu tertinggi mengalami myopia sebanyak 40 (43.3%) responden, presbiopia sebanyak 28 (30.1%) responden, Glukoma sebanyak 14 (15.1%) responden dan yang mengalami katarak sebanyak 11 (11.8%) responden. Namun dari lansia mengalami penyakit tersebut yang menggunakan kacamata hanya 24 (25.8%) responden. Simpulan: Lansia di dusun Kembang mengalami berbagai penyakit mata seperti presbiopia, myiopia, katarak dan glukoma namun yang menggunakan alat bantu penglihatan kacamata hanya 25.8% saja.   Kata Kunci: Glukoma; Katarak; Myopia; Presbiopia.